Pengaruh Kualitas Produk Harga Lokasi dan Promosi Terhadap Kepuasan Konsumen Pada Toko Kue AHK Keju di Kecamatan Teluk Segara - Al Hidayat, Rahmat; Charolina, Ovita; Afriani, Widra (Jurnal Adminitrasi Bisnis Nusantara, 2024)
The aim of this research is to find out the relationship between product quality, price, location and promotion on consumer satisfaction at the AHK Cheese cake shop, to find out how much influence product quality has on consumer satisfaction at the AHK Cheese cake shop, how much influence price has on consumer satisfaction at the shop AHK Cheese cake, how much influence does location have on consumer satisfaction at the AHK Cheese cake shop, how much influence does promotion have on consumer satisfaction at the AHK Cheese cake shop, how big is the influence of product quality, price, location and promotion on consumer satisfaction at the AHK Cheese cake shop in Teluk Segara District. Data collection methods include library research, observation, documentation and questionnaires. Data analysis techniques using data quality tests, classical assumption tests, multiple linear regression tests and hypotheses. The research results showed that product quality, price, location and promotion together (simultaneously) had a significant effect on consumer satisfaction at the AHK Cheese cake shop with a sig value of 0.000 < 0.05. The influence of product quality on consumer satisfaction at the AHK Cheese cake shop in Teluk Segara District is 8.3%, while the remaining 91.7% is explained by other factors. The magnitude of the influence of price on consumer satisfaction at the AHK Cheese cake shop in Teluk Segara District is 37.1% while the remaining 61.9% is explained by other factors. The influence of location on consumer satisfaction at the AHK Cheese cake shop in Teluk Segara District is 26.7% while the remaining 73.3% is explained by other factors. The influence of promotion on consumer satisfaction at the AHK Cheese cake shop in Teluk Segara District is 78.7%, while the remaining 21.3% is explained by other factors. The influence of product quality, price, location and promotion on consumer satisfaction at the cake shop. The AHK for Cheese in Teluk Segara District is 79.2% while the remaining 20.8% is explained by other factors. Thus, the AHK Cheese cake shop should also try to improve product quality, still pay attention to the prices set, and look for a more strategic location